FACTORS RELATED TO MOTHERS' VISITS BRINGING TODDLERS TO PERMATA HATI POSYANDU IN DRIEN RAMPAK VILLAGE, WEST ACEH REGENCY IN 2024 - Rina Novita; Itza Mulyani; Ravi Masitah; Sufyan Anwar (PT. Radja Intercontinental Publishing, 2025)
The activeness of visits to the posyandu is crucial for monitoring children's health and nutrition by regularly weighing toddlers' weight with the Kartu Menuju Sehat (KMS, or Healthy Growth Card). This study aims to determine the factors related to mothers' visits with their toddlers to Posyandu Permata Hati in Drien Rampak Village, West Aceh Regency, in 2024. The quantitative study uses an observational analytic design with a cross-sectional approach. The population consists of all mothers with toddlers aged 0-59 months, with a total sampling method of 87 mothers. The instrument used a questionnaire covering all variables, including maternal knowledge, education, occupation, family support, and visits to the posyandu. The analysis uses the Chi-Square test. The results show no relationship between maternal knowledge (p=1.000) and education (p=1.000), but there is a relationship between maternal occupation (p=0.004) and family support (p=0.000) with visits to the posyandu. The suggestion for the posyandu is to hold regular educational activities to increase mothers' awareness of the importance of visiting the posyandu. For working mothers or those with various other activities, it's essential to schedule time to bring their toddlers to the posyandu.